2007
DOI: 10.1038/sj.mp.4001977
|View full text |Cite
|
Sign up to set email alerts
|

More evidence supports the association of PPP3CC with schizophrenia

Abstract: Calcineurin is a calcium/calmodulin-dependent protein phosphatase composed of two subunits, a regulatory subunit of calcineurin B (CNB) and a catalytic subunit of calcineurin A (CNA). PPP3CC is the c isoform of CNA located at the chromosome 8p21.3 region. To evaluate the association between PPP3CC and schizophrenia in the Taiwanese population, 10 single nucleotide polymorphism (SNP) markers across the gene were genotyped by the method of MALDI-TOF in 218 schizophrenia families with at least two affected siblin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 46 publications
2
38
0
Order By: Relevance
“…In contrast to most other tissues, parts of the brain produce the CnA␥ isoform. The gene encoding this isoform has been named a candidate susceptibility gene for schizophrenia, because singlenucleotide polymorphisms within and near this gene have been associated with schizophrenia in different ethnic groups (18,19 ).…”
Section: Brainmentioning
confidence: 99%
“…In contrast to most other tissues, parts of the brain produce the CnA␥ isoform. The gene encoding this isoform has been named a candidate susceptibility gene for schizophrenia, because singlenucleotide polymorphisms within and near this gene have been associated with schizophrenia in different ethnic groups (18,19 ).…”
Section: Brainmentioning
confidence: 99%
“…24 However, only a few microarray analysis using immortalized lymphocytes from patients with schizophrenia have been reported. [25][26][27] Whether immortalized lymphocytes are an appropriate alternative to neuronal tissue remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…1-4 Numerous family-based linkage or population-based studies have identified a large set of schizophrenia-associated loci; however, many have not been replicated either in a different ethnic background, 5,6 or in the same ethnic background but in a diverse geographical location. 7,8 Although the number of risk loci is rather large, only a small portion overlaps with the large cumulative pool of genes that have shown changes of expression in the disease state. This suggests a heavily weighted portion of the functionally affected genes in schizophrenia that is unlikely to result directly from the susceptibility loci.…”
Section: Introductionmentioning
confidence: 99%